An Analysis of the Post-Globalization State of International Trade Settlement Techniques: Exploring the Evolution and Impact of International Trade Settlement Techniques in the Post-Globalization Era (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The landscape of international commerce was drastically altered as a result of the accelerationof globalization in the late 20th and early 21st centuries. As the world's economies grew increasinglyintertwined and trade volumes increased, the need for secure and efficient trade settlement methodsskyrocketed. Due to the increasing complexity of international trade and the rise of new economicpowers, traditional settlement procedures were increasingly put to the test. The purpose of this researchis to examine the evolution of international trade settlement methods after globalization. From theearliest phases of globalization to the current day, settlement methods are examined in depth. It delvesinto the background of current settlement patterns and the main elements that prompted the change. Thefunction of financial institutions in supporting international trade transactions and the effects oftechnology developments on settlement systems are also explored in this study.